Effect of Hybrid Composition and Volume Fraction on Microstructure and Microhardness of 7075 Aluminum Alloy via Friction Stir Processing - Jaafar, Nur Nabila Najad (IRC, 2020)
Most advanced engineering applications that require monolithic material structures with a broad variety of properties are hard to obtain. Composites in particular have enhanced substantial mechanical and tribological properties to fulfill the needs of the essential field of surface engineering. Friction stir processing (FSP) technology turns up as a promising technique in modifying microstructure and fabricating surface composites. Owing to their low density and high strength, aluminum alloys overtake steel alloys in various applications. Despite that, aluminum alloys are restricted under different loading conditions due to their weak surface properties. Hence, hybrid surface composites of aluminium matrix reinforced with Fly Ash (FA) and Graphite (Gr) are fabricated via FSP for this project. Experiments are conducted to study the relationship and find the optimum value of two parameters which are hybrid composition (60:40, 75:25, 90:10) and volume fraction (4%, 8%, 12%) of the reinforcement particles with regards to microhardness and microstructural characterization.